2009
DOI: 10.1080/09638280801945709
|View full text |Cite
|
Sign up to set email alerts
|

Parents' conceptions of intensive group training. The case of cerebral palsy

Abstract: Purpose:The aim was to explore what wants and needs intensive group training (IGT) fulfil for parents to children with CP and what problems that may arise due to participation. Methods:A phenomenograpical approach was used. Semi-structured interviews were conducted to elicit information about what participation means to parents. Results: Five overarching categories expressing positive functions of IGT were identified: IGT as knowledge promotion, as a complementary training resource, as a bracket to ordinary li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Finally, reported group outcomes are similar to those presented in the literature: groups increase feelings of support and well-being, decrease families' feelings of isolation and provide opportunities for children to develop and practice various skills (Eliasson, et al, 2009; Graham & Avent, 2004; Kayihan, 2001; Hendriks, De Moor, Oud & Savelberg, 2000; LaForme Fiss & Effgen, 2007; LaForme Fiss et al, 2009;Odman, et al, 2009). Group benefits on self-esteem were also reported.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Finally, reported group outcomes are similar to those presented in the literature: groups increase feelings of support and well-being, decrease families' feelings of isolation and provide opportunities for children to develop and practice various skills (Eliasson, et al, 2009; Graham & Avent, 2004; Kayihan, 2001; Hendriks, De Moor, Oud & Savelberg, 2000; LaForme Fiss & Effgen, 2007; LaForme Fiss et al, 2009;Odman, et al, 2009). Group benefits on self-esteem were also reported.…”
Section: Discussionsupporting
confidence: 62%
“…Groups may however create opportunities for new forms of therapeutic relationships within rehabilitation programs, such as the peer support provided among families. Given that a group's objectives may be more holistic and less discipline-specific, our results suggest that children's well-being and social participation Therapists doubts about service quality might be explained by the professional 'dilemma' coined by King et al (2006) and referring to a focus on discipline-and skill-specific developmental goals rather than those related to children's well-being and social participation.Finally, reported group outcomes are similar to those presented in the literature: groups increase feelings of support and well-being, decrease families' feelings of isolation and provide opportunities for children to develop and practice various skills (Eliasson, et al, 2009; Graham & Avent, 2004; Kayihan, 2001; Hendriks, De Moor, Oud & Savelberg, 2000; LaForme Fiss & Effgen, 2007; LaForme Fiss et al, 2009;Odman, et al, 2009). Group benefits on self-esteem were also reported.…”
supporting
confidence: 62%
“…In the systematic review, individual training, such as home training, showed more promising improvements than group training, found in the CE studies (67,70,(140)(141)(142). Ødman et al (143), who investigated the effects of CE and included children 3-16 years old, suggested that older children benefitted more from group training than younger children. Because the children in the RCT were six years old or younger, and half of them had GMFCS levels IV-V, this fact might indicate that some of the children were too young or were not sufficiently mature cognitively to benefit from the added effect of group training.…”
Section: Amount and Duration Of Intensive Trainingmentioning
confidence: 99%
“…[4] Caregivers can increase their information by involvement in support groups. [20] They also need to trust the information provided through support groups. Information from support groups gives caregivers feelings of competence and well-being, which potentially meets their needs.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] In addition to formal knowledge, sharing experiences in support groups also enables caregivers to gain practical knowledge and skills for the day-to-day management of their CCP. [17,20] 3.2 Financial needs Support with financial needs is a recurring need expressed by caregivers. The majority of financial needs identified in the literature were related to the financial burden associated with the cost of equipment, treatments, therapies, insurance, and access to community services.…”
Section: Informational Needsmentioning
confidence: 99%